2020
DOI: 10.3390/ijerph17155625
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Counseling in Primary Care in Germany—An Integrative Review

Abstract: Physical activity counseling in primary health care is regarded as a useful complementary preventive and therapeutic measure and is advocated by leading public health institutions. This integrative review summarizes the available data on physical activity counseling in primary care in Germany. A systematic literature search in various databases (peer reviewed and grey literature) was carried out for quantitative and qualitative studies on physical activity counseling and use of “Exercise on Prescription”. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
0
16
0
7
Order By: Relevance
“…We must also note that medical professionals must likewise become better equipped to interact with the fitness sector. Based on recent studies, general practitioners show very low levels of knowledge about physical activity guidelines and exercise promotion in primary health care is very rare [24][25][26]. According to Füzéki et al [24] "strengthening the topics of physical activity and health and physical activity counselling in medical curriculum is strongly recommended" as it would prepare health care providers for effective collaboration with fitness professionals to support increased physical activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…We must also note that medical professionals must likewise become better equipped to interact with the fitness sector. Based on recent studies, general practitioners show very low levels of knowledge about physical activity guidelines and exercise promotion in primary health care is very rare [24][25][26]. According to Füzéki et al [24] "strengthening the topics of physical activity and health and physical activity counselling in medical curriculum is strongly recommended" as it would prepare health care providers for effective collaboration with fitness professionals to support increased physical activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…16 PAC interventions promoting PA may provide clinically relevant effects. 17 The aim of our study was to investigate the effects of presurgical aerobic dance-based exercise programme (PSADBE) and PAC programme compared to only PAC on lower extremity functions in people with morbid obesity awaiting bariatric surgery (PMOABS). We hypothesized that the PSADBE compared to the PAC programme results in higher functional capacity, physical fitness, PA, fatigue and quality of life (QoL) outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…4 The prevalence of PA counselling in PHC varies. 5,6 A study reported a discrepancy between physician-reported (high: 90% reported offering PA counselling) and patient-reported (low: 8.6% reported receiving PA counselling) prevalence. 5 This may reflect the different perspectives of health care providers and patients.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 A study reported a discrepancy between physician-reported (high: 90% reported offering PA counselling) and patient-reported (low: 8.6% reported receiving PA counselling) prevalence. 5 This may reflect the different perspectives of health care providers and patients. A major target for PA counselling is patients with chronic illnesses (eg, diabetes mellitus, hypertension, and osteoarthritis).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation